2023
DOI: 10.21203/rs.3.rs-2821412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antioxidant potential, lipid profile and sensory attributes of a functional yogurt formulated with hydroethanolic extract of Mentha Piperita L.

Abstract: This study aims to quantify and identify phenolic compounds in the hydroethanolic extract of Mentha piperita L. harvested in the Algerian Sahara by colorimetric and LC-MS/MS analysis, assess its antioxidant capacity by DPPH and ABTS assays and examine the impact of its inclusion at 2 to 6% rates on sensory and oxidative properties (DPPH, ABTS, TEBARS) and the lipid profile analyzed by GC-FID in steamed yoghurt. The extract contained 41.29 mg GAE/ml total phenolics, 22.45 mg QE/ml total flavonoids and only 0.59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The results show that DPPH-scavenging activity increased with PuE addition levels, where the antioxidant activity in PuE 250-yogurt increased 2.5-fold over the control on the first day of storage; % AA continued to increase by 4.4-fold at the end of storage. Our results agree with Guemidi et al [73], who found a significant percentage increase in the antioxidant activity of yogurt, 40%, compared to the control yogurt when Mentha piperita extract was added to the formulation. Cho et al [74] reported a reduction in the scavenging activities of DPPH radicals during storage, which may be because a complex was formed between the polyphenols in the extract and the yogurt proteins, thereby reducing the restoration of the polyphenols and their antioxidant effect [72].…”
Section: Antioxidant Content In Yogurt Samples Supplemented With Purs...supporting
confidence: 93%
See 1 more Smart Citation
“…The results show that DPPH-scavenging activity increased with PuE addition levels, where the antioxidant activity in PuE 250-yogurt increased 2.5-fold over the control on the first day of storage; % AA continued to increase by 4.4-fold at the end of storage. Our results agree with Guemidi et al [73], who found a significant percentage increase in the antioxidant activity of yogurt, 40%, compared to the control yogurt when Mentha piperita extract was added to the formulation. Cho et al [74] reported a reduction in the scavenging activities of DPPH radicals during storage, which may be because a complex was formed between the polyphenols in the extract and the yogurt proteins, thereby reducing the restoration of the polyphenols and their antioxidant effect [72].…”
Section: Antioxidant Content In Yogurt Samples Supplemented With Purs...supporting
confidence: 93%
“…Lipid peroxidation was evaluated at intervals of 0, 7, 14, 21, and 30 days of storage at 4 • C of experimental yogurts prepared with PuE (50, 150, and 250 µg/mL) by measuring MDA according to the method of Guemidi et al [73]. Ten grams of yogurt were put in glass tubes containing ice to prevent oxidation, and then 100 µL of ascorbic acid and 20 mL of a TCA (5%, w/v) were added.…”
Section: Malondialdehyde (Mda) Determinationmentioning
confidence: 99%